Pengaruh Nutritional Support terhadap Luaran Klinis pada Pasien Intensive Care Unit: Effect of Nutritional Support on Clinical Outcomes of Intensive Care Unit Patients - Harti, Leny Budhi; Dini, Cleonara Yanuar; Fatoni, Arie Zainul (Universitas Airlangga, 2024)
Background: Nutritional support is a globally acknowledged standard of care for critically ill patients, forming an integral component of clinical therapy in Intensive Care Units (ICUs) to enhance overall clinical outcomes. Objectives: This study aimed to assess the impact of enteral nutritional support on clinical outcomes in ICU patients. Methods: This research adopted a systematic review approach, focusing on Randomized Controlled Trial (RCT) studies conducted between 2010 and 2020. The review adhered to the PRISMA guidelines. The clinical outcomes studied included length of stay in the hospital, length of stay in the ICU, and mortality. Discussion: Among 897 reviewed articles, only 6 articles were relevant. The study respondents were ICU in patients who received enteral formula, both in the control and intervention groups. The intervention group received an enteral formula featuring modified energy (normocaloric and high protein) and nutrients (enriched with pectin and immunse-modulating nutrients). Nutritional support in the form of enteral nutrition has varying effects on the length of hospitalization, ICU, and mortality. Conclusions: No significant difference was observed in ICU and hospital stays between patients receiving standard enteral/hypocaloric/high protein nutrition and those receiving enteral nutrition enriched with pectin or immune-modulating nutrients. However, patients receiving enteral nutrition with immune-modulating nutrients experienced a reduced length of hospitalization. The administration of immune-modulating nutrients was associated with an increased risk of mortality at 60 and 28 days in critically ill patients.